Alat Bukti Sumpah dalam Perspektif Hukum Islam - Khairatin Azizah; Muammar bin Mosni; Kholili Anam; Mega Ayu Ningtyas (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2021)
Abstract: This article discusses proof through oath from the perspective of Islamic law. This article was written based on the results of a qualitative literature review and the data collected were analyzed inductively. An oath is a statement made by someone who carries the name of God. An oath made in the name of God may not be used as a toy or placed on something that is not reasonable, even if it is not intentional, because an oath has consequences for the person who carries out the oath. An oath according to Islamic law is an utterance accompanied by the mention of the name of Allah, intending to convince the other party about the veracity of the utterance of the oath. If what is to be convinced is contrary to the heart of the speaker, then he is willing to receive sanctions from Allah. In Islamic law, an oath made by someone who is litigating in court can be used as evidence. Keywords: Oath, court, Islamic law. Abstrak: Artikel ini membahas tentang pembuktian melalui sumpah dalam perspektif hukum Islam. Atikel ini ditulis berdasarkan hasil kajian pustaka yang bersifat kualitatif dan data yang terkumpul dianalisis secara induktif. Sumpah merupakan pernyataan yang dilakukan oleh seseorang dengan membawa nama Tuhan. Sumpah yang dilakukan atas nama Tuhan tidak boleh dijadikan mainan atau ditempatkan pada hal yang tidak wajar, meskipun dengan tidak sengaja, karena sumpah memiliki konsekuensi kepada orang yang melaksanakan sumpah tersebut. Sumpah menurut hukum Islam merupakan suatu ucapan yang yang disertai dengan menyebut nama Allah, dengan tujuan meyakinkan pihak lain tentang kebenaran ucapan yang bersumpah. Apabila apa yang hendak diyakinkan itu bertentangan dengan isi hati pengucap, maka ia bersedia mendapatkan sanksi dari Allah. Dalam hukum Islam, sumpah yang dilakukan oleh seseorang yang berperkara di pengadilan dapat dijadikan sebagai alat bukti. Kata Kunci: Sumpah, pengadilan, hukum Islam.